Internal Granuloma - Present State of the Problem - J. Netolický; E. Záhlavová (Czech Dental Chamber, 2007)
It has been generally acknowledged that internal granuloma (internal resorption, granuloma internum) originates on the basis of disorder of pulp metabolism, associated with degenerative processes, which follow to chronic inflammation of tooth pulp.The authors describe the present state of the problem in teeth with internal granuloma. In a long-term clinical study they document the occurrence of 25 internal granulomas. Their possible etiology is evaluated, the clinical course is described and present possibilities of treatment are discussed in particular.In suitable cases the authors employ repeated filling of the root canal with pure preparations of calcium hydroxide, consider suitable techniques for filling the root canal and draw attention to suitable materials for reconstruction of damaged root.